OP0004 THE EXPRESSION OF INTERFERON-STIMULATED GENES IN PERIPHERAL BLOOD OF PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS (SLE) ASSOCIATES WITH AFRICAN ANCESTRY. (2nd June 2020) - Wilhelm, T.; Zahid Siddiqi, K.; Jacobsen, S.
Abstract : Background: Type I Interferons (IFNs), and especially INF-alpha, play a crucial role in the pathogenesis of SLE. Interferon-stimulated genes (ISGs) are generally up-regulated in SLE patients. Their pattern of up-regulation is often termed as an IFN signature. Even though composite IFN-scores are already used to express the up-regulation of the IFN-system, e.g. in studies testing therapeutic anti-IFN-antibodies, we are still lacking an in-depth understanding of the IFN signature. Objectives: To summarize the available data on the expression of ISGs in peripheral blood of patients with SLE compared to healthy controls; to assess which ISGs are most up-regulated in SLE patients; and to analyse if up-regulations of 6 ISGs typically used in IFN-scores [1, 2] are associated with SLE disease activity and ethnicity. Methods: The electronic databases PubMed and EMBASE were searched using the terms "interferon signature", "SLE", "interferon-stimulated genes", "microarray" and "gene expression" with inception date until Jan. 28, 2020. Original case-control studies containing quantitative data of ISG expression were included. Exclusion criteria were studies with animal models, clinical trials of drug treatment and studies with ex vivo stimulation of cells prior to gene-expression analysis. Fold changes (FCs) (ISG expression in SLE/ISG expression in healthy controls) for the ISGs analysed in each study were extracted. FCs were plotted gene-wise on a heatmap for studies analysing ≥ 7 genes and for genes that were analysed in ≥ 5 studies. Cluster analysis using principle component analysis (PCA) and association analyses using generalized linear modelling (GLM) were performed for 6 ISGs (IFI27, IFI44, IFI44L, RSAD2, PRKR and IFIT1) as well as disease activity and ethnicity (SPSS). Results: 16 case-control studies comprising a total of 851 SLE patients were included in the analyses, see Tab. 1. 24 ISGs had an average FC of ≥ 4. IFI27, RSAD2, IFI44L, IFI44, HERC5 and IFIT5 had an average FC > 6. The heatmap showed great variation in the expression of ISGs within the individual studies but also gene-wise between the studies, see Fig. 1 . The inter-study variation was statistically explored for the selected 6 ISGs. PCA showed that PRKR, RSAD2, IFIT1, IFI44 and IFI44L clustered with African ancestry, see Fig. 2 . Subsequent GLM confirmed that RSAD2 and PRKR were positively associated with African ancestry. However, none of the 6 ISGs were positively correlated with disease activity. Conclusion: The degree of up-regulation of ISGs in SLE patients shows considerable variation within and between the individual studies. However, a pattern of up-regulation clearly emerges. We find a clustering of 5 prominent genes of the IFN signature (PRKR, RSAD2, IFIT1, IFI44 and IFI44L) and a positive correlation of RSAD2 and PRKR with African ancestry, pointing to the need to take ethnicity into account when using the IFN signature. Our results do not support the use of the IFN signature as traditionally defined as a surrogate marker for disease activity. References: [1]Kirou, K.A. et. al. Arthritis Rheum. 52, 1491–1503 (2005) [2]Morand E.F. et. Al. N Engl J Med. (2019) Disclosure of Interests: None declared